2010
DOI: 10.1002/cncr.24919
|View full text |Cite
|
Sign up to set email alerts
|

Radiation monotherapy as regional treatment for lymph node‐positive Merkel cell carcinoma

Abstract: BACKGROUND:Merkel cell carcinoma (MCC) is an aggressive cutaneous malignancy with a high risk of lymph node involvement. To the authors' knowledge, few data have been published to date regarding the optimal regional therapy for lymph node‐positive patients. This cohort study was performed to analyze the outcomes of patients with lymph node‐positive MCC treated with lymph node irradiation as definitive therapy compared with completion lymphadenectomy (CLND).METHODS:Fifty patients with lymph node involvement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 53 publications
8
102
0
8
Order By: Relevance
“…Fang et al [40] showed high rates of local control in lymph node basins for pathologically involved nodes treated with primary radiotherapy compared with lymphadenectomy AE radiotherapy. Those with 'microscopic' regional disease (n ¼ 26) who received either radiotherapy alone (n ¼ 19), lymph node dissection alone (n ¼ 3) or both (n ¼ 4), had 2 year regional recurrence-free survival of 100%.…”
Section: Primary Radiotherapymentioning
confidence: 98%
“…Fang et al [40] showed high rates of local control in lymph node basins for pathologically involved nodes treated with primary radiotherapy compared with lymphadenectomy AE radiotherapy. Those with 'microscopic' regional disease (n ¼ 26) who received either radiotherapy alone (n ¼ 19), lymph node dissection alone (n ¼ 3) or both (n ¼ 4), had 2 year regional recurrence-free survival of 100%.…”
Section: Primary Radiotherapymentioning
confidence: 98%
“…However, it is unknown if this treatment should consist of radiotherapy and/or surgery. In the study by Fang et al, 42 after a positive SLNB result, 19 patients received radiotherapy to the lymph node basin, 3 underwent completion lymphadenectomy, and 4 underwent both completion lymphadenectomy and radiotherapy, and no patients developed regional disease recurrence. The authors of this study concluded that in terms of regional disease control completion lymphadenectomy was comparable with radiotherapy.…”
Section: J Am Acad Dermatolmentioning
confidence: 99%
“…Although most clinicians recommend surgery to achieve pathological staging [3][4][5] this is not always undertaken and there is evidence that radiotherapy alone may be efficacious for macroscopic nodal disease. 2,6,7 There is also evidence that adjuvant radiotherapy after surgery is associated with improved locoregional control [8][9][10][11] and survival, 12 however this has been challenged by others. 13 Similarly, the role of chemotherapy is currently under investigation.…”
mentioning
confidence: 97%
“…1,2 Because of the rarity of this tumor and the lack of prospective clinical trials, controversies exist regarding the optimal staging 3 and treatment 4 of this disease.…”
mentioning
confidence: 99%